Amyloid imaging and Alzheimer’s disease: the unsolved cases - O’Sullivan, Michael J. (Brain, 2016)
This scientific commentary refers to ‘Atrophy, hypometabolism and clinical trajectories in patients with amyloid-negative Alzheimer’s disease’, by Chételat et al. (doi:10.1093/brain/aww159).